2015
DOI: 10.1186/s40249-015-0061-1
|View full text |Cite
|
Sign up to set email alerts
|

On dogs, people, and a rabies epidemic: results from a sociocultural study in Bali, Indonesia

Abstract: BackgroundPreviously free of rabies, Bali experienced an outbreak in 2008, which has since caused a large number of human fatalities. In response, both mass dog culling and vaccination have been implemented. In order to assess potential community-driven interventions for optimizing rabies control, we conducted a study exploring the relationship between dogs, rabies, and the Balinese community. The objectives of this study were to: i) understand the human-dog relationship in Bali; ii) explore local knowledge, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
7
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 25 publications
5
62
7
9
Order By: Relevance
“…Over 70% of households own dog(s), and Balinese identify dogs as culturally important, with dogs revered in Balinese Hinduism (24). Dogs are reportedly mainly kept to guard the house, with some Balinese believing dogs can alert their owners against evil spirits (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 70% of households own dog(s), and Balinese identify dogs as culturally important, with dogs revered in Balinese Hinduism (24). Dogs are reportedly mainly kept to guard the house, with some Balinese believing dogs can alert their owners against evil spirits (24).…”
Section: Discussionmentioning
confidence: 99%
“…Over 70% of households own dog(s), and Balinese identify dogs as culturally important, with dogs revered in Balinese Hinduism (24). Dogs are reportedly mainly kept to guard the house, with some Balinese believing dogs can alert their owners against evil spirits (24). Our surveys showed that most Bali dogs were allowed to roam (>90% in rural areas, Table 1), which can lead to perceptions of a “stray dog problem” and pose a challenge for achieving and demonstrating high levels of vaccination coverage.…”
Section: Discussionmentioning
confidence: 99%
“…We found that in Chitwan District (Nepal) some responders admitted killing puppies by drowning or mentioned they knew others that used this method, as well as strychnine, for killing dogs. The sex ratio of 2 : 1 males/females recorded in other Nepalese towns (Acharya and Dhakal, ; HART, unpublished) suggested that more female puppies are killed than males, because females produce unwanted litters or attract males when in oestrus (Totton et al., ; Acharya and Dhakal, ; Widyastuti et al., ). This is clearly an area where sterilization and public education might increase acceptance of female dogs and reduce inhumane killing.…”
Section: Discussionmentioning
confidence: 99%
“…In Samoa, 30% of respondents mentioned that they knew someone who had harmed or killed a dog to reduce problems associated with canine overpopulation (Farnworth et al., ). In Bali, 74% respondents mentioned that government‐driven mass culling of free‐roaming dogs had occurred in their village in response to rabies outbreaks, but also that puppies, and particularly females, were routinely abandoned near restaurants and rubbish dumps but not killed due to religious beliefs on non‐violence (Widyastuti et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation